Differences in Innate Immunologic Response to Group B Streptococcus Between Colonized and Noncolonized Women. Issue 3 (2001) - Smith, Jennifer M.; Respess, Rachel H.; Chaffin, David G.; Larsen, Bryan; Jackman, Susan H.
Abstract : Objective: To evaluate the functional capacity of granulocytes and monocytes from pregnant and nonpregnant women in relation to group B streptococcus (GBS) colonization status. Methods: Engulfment of fluorescent GBS by peripheral blood phagocytes from GBS-colonized and noncolonized women was measured by flow cytometry. Intracellular superoxiode generated in response to GBS challenge to monocytes and granulocytes enriched from peripheral blood of these women was also measured by flow cytometry, and extracellular superoxide was determined by colorimetric assay. Results: Monocytes and granulocytes from pregnant, GBS-colonized women engulfed significantly greater numbers of GBS than phagocytes from pregnant, noncolonized women. No difference in intracellular superoxide production was detected between any of the groups of women; however, monocytes from pregnant, colonized women released significantly more superoxide into the extracellular milieu than did granulocytes from the same women. No differences in extracellular release of superoxide were observed among noncolonized women whether they were pregnant or not. Conclusions: Monocytes from pregnant, colonized women engulf more GBS and release more of the superoxide into the extracellular environment, where it is unlikely to be an effective defense mechanism against intracellular bacteria. This suggests that components of the innate immune system that should serve in a protective role may function suboptimally, thereby contributing to the colonization process by GBS.